Amplification of zinc finger protein gene (ZFX) as identification marker for malaysian bovine species - Mohd Hafiz, Mail (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
PCR-RFLP technique was developed to identify three endogenous bovine species; KK Cattle, Bali Cattle and Seladang. Total genomic DNA from six bovine samples was isolated from leukocyte preparation. PCR amplification of these genomic DNA using P 1- 5EZ and P2-3EZ primers for zfx gene resulted in a fragment approximately 420bp in size from all samples. After restriction analysis, six enzymes were determined to be used to distinguish all the three species. The enzymes include Bpm I, Nla IV, Hin 4I, Taq II, Tsp RI and Alu I. Three bovine species can be distinguished from each other by using specific enzyme that cut only one zfx sequence of the species. Bpm I and Nla IV could cleave the 416bp fragment in KK cattle, but there was no cutting site in the other two species. These two enzymes produce a unique restriction site and used as identification marker for the KK cattle. Hin 41 and Taq II could cleave the 419bp zfx sequence of Bali cattle and directly distinguish it among others. There was no specific enzyme for Seladang. If there was no cut by the four stated enzyme, the probability of the sample was Seladang. Alu I and Tsp RI enzyme could be used for confirmation purpose. Both enzymes cleaved all zfx sequence of the three bovine species but at different position. Digestion using all the enzymes produces a specific marker for identification of bovine species. This technique can be widely used for screening test in investigation of industrial food, support conservation cattle breeding plans and identification of newborn cattle.